2015
DOI: 10.1364/ol.40.001861
|View full text |Cite
|
Sign up to set email alerts
|

Multi-resonant optical parametric oscillator based on 2D-PPLT nonlinear photonic crystal

Abstract: The aim of this work is to achieve an optical parametric oscillator based on two-dimensional periodically poled lithium tantalate (2D-PPLT) crystals that are designed to allow multiple reciprocal lattice-vector contribution to the quasi-phase matching scheme. We are particularly interested in the effect of the multi-wavelength parametric generation performed by the 2D nonlinear photonic crystal to achieve a multi-resonant optical parametric oscillator. The performances are studied in terms of generation effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The existence of PBG enables the combination of nonlinear effects and PCs to generate many remarkable phenomena, such as PBG drift, [ 14 ] nonlinear induced self‐trapping, [ 15 ] second harmonic generation (SHG), [ 16 ] difference frequency, [ 17 ] optical bistability, [ 18 ] and optical parametric oscillators. [ 19 ] Among them, SHG has received extensive research attention since it can effectively extend the laser bandwidth and obtain the required light source frequency. In 1995, Trull [ 20 ] et al found that 1D NPCs structure with defects could enhance the excitation effect of SHG, and in 2004, Xu [ 21 ] et al found that PCs grating structures could simultaneously generate second and third harmonic and achieve phase matching.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of PBG enables the combination of nonlinear effects and PCs to generate many remarkable phenomena, such as PBG drift, [ 14 ] nonlinear induced self‐trapping, [ 15 ] second harmonic generation (SHG), [ 16 ] difference frequency, [ 17 ] optical bistability, [ 18 ] and optical parametric oscillators. [ 19 ] Among them, SHG has received extensive research attention since it can effectively extend the laser bandwidth and obtain the required light source frequency. In 1995, Trull [ 20 ] et al found that 1D NPCs structure with defects could enhance the excitation effect of SHG, and in 2004, Xu [ 21 ] et al found that PCs grating structures could simultaneously generate second and third harmonic and achieve phase matching.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we propose and experimentally demonstrate a Janus OPO based on quasi-phase-matching (QPM) configuration 43 47 for highly efficient output of highly pure, broadly tunable, and TC-controllable LG modes [Fig. 1(c)].…”
Section: Introductionmentioning
confidence: 99%
“…The fiber laser is another potential platform for broadband output of LG mode, but it suffers from low mode purity as well. 41,42 Here, we propose and experimentally demonstrate a Janus OPO based on quasi-phase-matching (QPM) configuration [43][44][45][46][47] for highly efficient output of highly pure, broadly tunable, and TC-controllable LG modes [Fig. 1(c)].…”
Section: Introductionmentioning
confidence: 99%
“…Since their proposal by Berger [1] and their first realization [2], χ (2) nonlinear photonic crystals (NPC) with a two-dimensional poling pattern have attracted great interest due to their potential applications in nonlinear optics [3][4][5][6][7][8][9], as well as in quantum optics for the generation and engineering of entangled states [10][11][12][13][14][15]. Considering parametric down-conversion (PDC) from an intense pump beam into twin photons or twin beams of lower frequencies, the vectors of the 2D reciprocal lattice associated to the nonlinear grating indeed offer multiple quasiphasematching (QPM) possibilities not encountered in more conventional one-dimensional structures.…”
Section: Introductionmentioning
confidence: 99%